Preparation, characterization and electrical behaviors of greenish single-chain polymeric molecule-via intramolecular ball type cobalt phthalocyanines/graphite oxide composites - Demirelli, Kadir; Abubakar, Abdullahi Musa; Tuncer, Hulya; Salih, Bekir (Elsevier, 2021)
The greenish single-chain polymeric molecule-ball type CoPc (SCPM-ball type CoPc) was prepared via the intramolecular formation of cobalt phthalocyanine from polystyrene-co-poly[4,4 '-((((4-vinylbenzyl)azanediyl)bis(ethane-2,1diyl))bis(oxy))diphthalonitrile] [P(PNDEAMSt12%-co-St)] (linear copolymer precursor) under diluted conditions at 150 degrees C. The structure of SCPM-ball type CoPc was confirmed by FT-IR, MALDI-TOF-MS, UV and SEM. The conversion dependence of the experimental activation energy was readily determined by an isoconversional method. So, the Flynn-Wall-Ozawa (FWO) and Kissinger-Akahira-Sunose (KAS) showed that the linear copolymer precursor's activation energies were as average 128.7 kJ/mol and 124.0 kJ/mol and those of SCPM-ball type CoPc were average 161.9 kJ/mol and 153.8 kJ/mol, respectively. Conductivity mechanism of composites was suggested as Correlated Barrier Hoping (CBH). The linear copolymer precursor/graphite oxide (GO) composite has a significant performance for dielectric constant of 696.4 at 130 degrees C, but it was with a comparatively greater dielectric loss. Those of SCPM-ball type CoPc/14wt% GO increased virtually the same relative ratio. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Single chain polymer; Graphite oxide; Kinetic; Electrical properties; Ball type CoPc